Docking Studies for Multi-Target Drugs - Scotti, Luciana; J.B. Mendonca Junior, Francisco; M. Ishiki, Hamilton; F. Ribeiro, Frederico; K. Singla, Rajeev; M. Barbosa Filho, Jose; S. DaSilva, Marcelo; T. Scotti, Marcus (Current Drug Targets, 2017)
The most basic principle of drug action is found in the lock and key model, where the highest possible affinity for a target that also avoids side effects is desired. For many years this was understood as being “one drug, for one target, for one disease”, however researchers began to observe that certain diseases are best treated with multi-target drugs. In recent years, studies have sought out polypharmacological compounds acting on multiple targets against complex (multifactorial) diseases, such as cancer, neurodegenerative disease, and certain infections. One of the computational tools used in research for multifunctional drugs is Molecular Docking. Through this methodology of Computer-Aided Drug Design, we observe complexes formed between ligands and interesting targets (often many), for a particular disease. This review reports on docking studies as used in investigations of new multi-target compounds; it also shows the various ways that such studies are used in the search for multifunctional compounds.
Keywords: diseases